2012
DOI: 10.1016/j.ccr.2012.03.048
|View full text |Cite
|
Sign up to set email alerts
|

LKB1/STK11 Inactivation Leads to Expansion of a Prometastatic Tumor Subpopulation in Melanoma

Abstract: SUMMARY Germline mutations in LKB1 (STK11) are associated with the Peutz-Jeghers syndrome (PJS), which includes aberrant mucocutaneous pigmentation, and somatic LKB1 mutations occur in 10% of cutaneous melanoma. By somatically inactivating Lkb1 with K-Ras activation (±p53 loss) in murine melanocytes, we observed variably pigmented and highly metastatic melanoma with 100% penetrance. LKB1 deficiency resulted in increased phosphorylation of the SRC family kinase (SFK) YES, increased expression of WNT target gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
120
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(128 citation statements)
references
References 50 publications
6
120
0
Order By: Relevance
“…Consistent with previous work (Carretero et al, 2010;Liu et al, 2012), we observed delayed closure upon reintroduction of LKB1 compared with the null cells (Fig. 2 E).…”
Section: Loss Of Lkb1 Does Not Affect Invadopodia Formation In Melanosupporting
confidence: 82%
See 3 more Smart Citations
“…Consistent with previous work (Carretero et al, 2010;Liu et al, 2012), we observed delayed closure upon reintroduction of LKB1 compared with the null cells (Fig. 2 E).…”
Section: Loss Of Lkb1 Does Not Affect Invadopodia Formation In Melanosupporting
confidence: 82%
“…S1 A; Liu et al, 2012). We confirmed that reexpression of LKB1 (addback) promoted phosphorylation of AMPK and its downstream effector acetyl-CoA carboxylase in three LKB1-deficient cell lines (LKB498, LKB878, and TKL2; Fig.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…Disruption of polarity, as altered metabolism, is a hallmark of epithelial cancer progression [11], and the relative roles of these processes downstream of LKB1 in growth control is an area of active investigation. Indeed, inactivation of LKB1 produces dramatic invasive and migratory phenotypes in different cancer models [12][13][14]. The findings of Jeon et al [9] may thus presage that the LKB1-AMPK axis is only a minor component of the LKB1 tumor suppressor program compared to its functions in metabolic adaptation and cell survival.…”
mentioning
confidence: 85%